EFFECTIVENESS OF CREDIT MANAGEMENT SYSTEM ON LOAN PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Njeru, Michael; Mohhamed, Dr Shano; Wachira, Mr. A (International Journal of Finance and Accounting, 2017)
Purpose: the purpose of this study was to analyze effectiveness of credit management system on loan performance of commercial banks in Kenya. Methodology:Descriptive research design was used. The population comprised of 86 respondents. That is, one credit manager and one credit officer from one branch of each of the 43 commercial banks registered with central bank of Kenya as at this year. A census study was conducted since the target population was small. Data was collected using a self-administered questionnaire through drop and pick later method. The questionnaire was both open and closed ended. Test retest method was used to ensure reliability while piloting was used to check the validly of the research instrument .data was analyzed using to frequencies, percentages and means. Correlation was used to compute the degree of association between variable. The hypothesis was tested using chi square. Data was thereafter presented using table and pie charts. Results:The study established that credit terms has an effect on performance, just like credit appraisal was equally found to be very important in influencing performance of commercial banks. Similarly, a stringent policy was found to have a far greater influence to performance than a libel policy Policy recommendation: It was then recommended the character of the borrower, the current capacity and collateral attached should carry a lot of weight in the appraisal. In addition, credit officer and client should be involved in formulation of credit terms and interest rates on loans reduced since these have an effect on loan repayment hence performance of commercial banks.